Delineation of the preferences and requirements of the human immunodeficiency virus type 1 dimerization initiation signal by using an in vivo cell-based selection approach. - Hussein, I; Ni, N; Galli, A; Chen, J; Moore, M; Hu, W (2010)
HIV-1 packages two copies of RNA into one particle, and the dimerization initiation signal (DIS) in the viral RNA plays an important role in selecting the copackaged RNA partner. We analyzed the DIS sequences of the circulating HIV-1 isolates in the GenBank database and observed that, in addition to the prevalent GCGCGC, GTGCAC, and GTGCGC sequences, there are many other minor variants. To better understand the requirements for the DIS to carry out its function, we generated a plasmid library containing a subtype B HIV-1 genome with a randomized DIS, infected cells with viruses derived from the library, and monitored the emergence of variants at different time points until 100 days postinfection. We observed rapid loss of viral diversity and found that the selected variants contained palindromes in the DIS. The "wild-type" GCGCGC-containing virus was a major variant, whereas GTGCAC- and GTGCGC-containing viruses were present at low frequencies. Additionally, other 6-nucleotide (nt) palindromic sequences were selected; a major category of the selected variants contained two GC dyads in the center of the palindrome, flanked by a non-GC dyad. Surprisingly, variants with GC-rich 4-nt palindromes were sustained throughout the selection period at significant frequencies ( approximately 12 to 38%); of these, variants containing the CGCGC sequence were observed frequently, suggesting that this sequence has a selection advantage. These results revealed that multiple sequences can fulfill the function of the HIV-1 DIS. A common feature of the selected DIS sequence is a 4- or 6-nt GC-rich palindrome, although not all sequences with these characteristics were selected, suggesting the presence of other unidentified interactions.